The Impact of Covid-19 containment on community pharmaceutical spending in Andalusia - Spain - Francisco Florido Alba; Nuria García-Agua; Angel Martín Reyes; Antonio Clavero Barranquero; Antonio J. Garcia Ruiz (Centro de Investigaciones y Publicaciones Farmaceuticas, 2021)
Background: In the field of health, the year 2020 will be remembered for testing (stressing) all health institutions and their forms of management (centralised and decentralised). The everyday activity of primary and hospital care was significantly altered by the introduction of telephone consultations, which reduce the number of visits to health centres or hospitals and are still relevant today in the face of successive waves of the pandemic. Objective: To analyse whether population confinement due to the COVID-19 pandemic had an impact on the dispensing of medications in community pharmacies and the associated spending during the period March-July 2020 in Andalusia (Spain). Methods: A time series analysis applying econometric model analysis techniques to confirm or rule out whether the lockdown caused by the COVID-19 pandemic had an impact on the dispensing of medications by community pharmacies and the associated expenditures. The variables used were the number of medication containers dispensed by community pharmacies (charged to the public funds of the Spanish National Health System) and the expenditure on prescription drugs, both in relation to the population. The analysis was performed within the region of Andalusia, which has 8,464,441 inhabitants. Results: The data obtained from the time series confirmed that there were no significant differences during the studied period between the number of medication containers actually dispensed and the number that would have been expected to be dispensed according to the trend in this variable for the sample period. The expenditure results followed the same pattern. Conclusions: The health crisis produced by the COVID-19 lockdown had no impact on medication consumption in Andalusia.